Arabic Language and Coaching: Efforts to Students’ Completion in Master of Arabic Education - Syamsul Arifin; Mauidlotun Nisa; Darsita Suparno (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
This study aims to reveal the coaching efforts made by lecturers, supervisors, and examiners of Arabic Language Masters Department (MPBA) students at UIN Syarif Hidayatullah Jakarta. This research is qualitative with a psychological approach. The primary data of this study were MPBA students who had dropped out but they succeeded in passing the last limit of their study period. In addition, the primary source of this research is the supervisor and examiner who intensively provide coaching to these students. Secondary data of this research are documents and information related to student conditions from the head of the department and staff as well as literature relevant to the research topic. The findings of this study are first, there are four stages carried out in the implementation of the GROW coaching model from Goal, Reality, Option, and Will. The Goal is graduating on time, Reality is position and condition of study progress, Option is insights to choose the best strategy, and Will is willing to complete studies. Second, even though they were late in completing their work, the quality of their thesis was quite acceptable and good. This proves that extrinsic motivation greatly affects their performance in thesis writing and overcoming difficulties in studying Arabic. The academic community's role in encouraging and motivating students is very large.